A Bacterial Evaluation Of Tonsillitis In Baghdad - AD’hlah, A. H; AL-Abdulwahed, L. S. A; ALkashaly, S. S. A (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A sample of 168 tonsillitic subjects (93 males and 75 females), livin g in Baghdad was evaluated microbiologically. The patients had an age range of 3-35 years. Four bacterial species were isolated and identified. They were P-haemolyt ic Streptococcus ,(39.3%) Staphylococcus aureus,(23.8% )Haemophilus injluenzae (20.8% )and a-haemolytic Streptococcus. (16.1 %)Sex differences in the prevalency of these bacteria were observed. Lancefield grouping of P-haemolytic Streptococcus showed five sera-groups (A, B, D, G and Non-typable). The A group dominated the list (72.7%), followed by the B group (13.6%), while the others shared a similar frequency (4.5% ).